Preliminary results of the fauna of «Cabeço de Amoreira» and «Cabeço de Arruda» (Muge, Portugal) - Lentacker, An (Trabalhos de Antropologia e Etnologia, 2020)
This preliminary archaeozoological study, analysed the fauna! material of two Mesolithic shell-middens: Cabeço de Amoreira and Cabeço de Arruda. A taphonomical division is made. We recognize consumption remains (mainly red deer, wild boar and aurochs); debris of artisanal activity (little gastropods, antler and teeth of red deer etc.); penecontemporaneous intrusives (herpetofauna, little mammals etc.) and late intrusives (rabbit, badger). The palaeoecological and palaeoeconomical analysis provides some information on the importance of each animal group in the diet of the Mesolithic Muge people and on the season of occupation of the two sites.